Evaluation Report. Oil Palm Portfolio. An Outcome Evaluation of FTA’s Research Portfolio on Oil Palm - Davel, R.; Claus, R.; Ichsan, M.; Belcher, B. (CGIAR Research Program on Forests, Trees and Agroforestry, 2020)
This report assesses the project design, implementation, and outcome realization of FTA’s research portfolio on oil palm in Indonesia. Four projects from the portfolio were selected for in-depth assessment: Supporting Local Regulations for Sustainable Oil Palm in East Kalimantan (EK), Governing Oil Palm Landscapes for Sustainability (GOLS), Oil Palm Adaptive Landscapes (OPAL), and Engendering RSPO Standards (ERS). The report documents and empirically tests whether and how intended portfolio outcomes were realized, with specific attention to the characteristics of projects’ design and implementation that contributed to changes in policy and practice within Indonesia’s oil palm sector.